Aspects from the evolution of past vegetation in Southern Transylvania (Sibiu region) - Sorina FĂRCAȘ; Ilie-Adrian STOICA; Ioan TANȚĂU (Studia Universitatis Babeș-Bolyai. Biologia, 2021)
The article reviews the results obtained through the palynological study of sequences obtained from the Sibiu region and adjacent areas. The oldest Upper Pleistocene sequences we refer to seem to reflect snapshots from the Last Glacial Maximum. The history of the Late Glacial and Holocene vegetation here is broadly part of the succession known for the territory of Romania, in the Carpathians and the surrounding areas of medium and low altitudes. The dynamics of the main forest and grasses taxa were highlighted, influenced both by natural factors and, more recently, by human activity. The reference area is characterized by the domination of the forests during the interstadials and by open landscape of forested steppe during the cold, stadial periods.